2018
DOI: 10.1007/s10157-018-1628-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of single-daily high-dose mizoribine therapy after cyclophosphamide in young children with steroid-dependent nephrotic syndrome

Abstract: Single daily high-dose MZR therapy after CPM therapy may have positive outcomes in young children with SDNS in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We previously demonstrated that high-dose mizoribine after cyclophosphamide therapy might be associated with favorable outcomes in pediatric patients with moderatedose (< 0.6 mg/kg/day) steroid dependence (Mizutani et al 2019). In the present study, most patients in the nonresponse group were able to discontinue SDNS after switching from mizoribine to cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that high-dose mizoribine after cyclophosphamide therapy might be associated with favorable outcomes in pediatric patients with moderatedose (< 0.6 mg/kg/day) steroid dependence (Mizutani et al 2019). In the present study, most patients in the nonresponse group were able to discontinue SDNS after switching from mizoribine to cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding 5,587 duplicates and 7,527 studies based on their titles and abstracts, 479 studies remained for full-text evaluation. Eventually, 15 studies (9)(10)(11)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were included in this systematic review and network meta-analysis. The study selection process is depicted in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…The 15 eligible studies (9)(10)(11)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) included 1053 pediatric patients with FRSDNS. The year of publication covered 2008 to 2022, and 9 countries were involved.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Since 2007, a single dose (375 mg/m 2 ; maximum, 500 mg) of rituximab (RTX; Rituxan, injection, Zenyaku Co., Tokyo, Japan) has been administered for patients with complicated SDNS after CsA or MMF treatment [14]. For young children with SDNS aged < 10 years and before puberty, cyclophosphamide (Endoxan, oral formulation, Shionogi Co., Osaka, Japan) was administered at a single daily dose of 2-2.5 mg/kg/day for 12 weeks (cumulative dosage, 200 mg/kg) [15]. For young children with low-dose steroid dependency, a single, daily, high dose of mizoribine (10 mg/kg/day maximum, 300 mg/day; Bredinine, oral formulation, Asahikasei, Tokyo, Japan) was offered as a treatment option [16].…”
Section: Treatment Protocolmentioning
confidence: 99%